Birth weight and the dynamics of early cognitive and behavioural development - Emilia Del Bono; John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2009)
In this paper we explore the impact of birth weight on childrens cognitive and behavioural outcomes using data from the UK Millennium Cohort Study. In order to deal with the endogeneity of birth weight we propose an eliminant estimator, which exploits the availability of multiple outcomes for the same individual at the same point in time. The results show that birth weight has significant but very small effects on male cognitive development at age 3 and on female cognitive and behavioural outcomes at age 3. We also find that birth weight affects age 5 outcomes only through previous achievements, and that the overall impact fades out over time. These findings call into question the effectiveness of birth weight as a policy target.
Keywords: 330